Analisis Pengungkapan Corporate Social Responsibility (CSR) Dalam Laporan Tahunan Terhadap Abnormal Return - Nana Umdiana; Kodriyah Kodriyah; Dien Sefty Framita (Akuisisi: Jurnal Akuntansi, 2021)
The aim of the study was to analyze the effect of disclosure of Corporate Social Responsibility (CSR) in the Annual Report on Abnormal Return in manufacturing companies with the food and beverage sub-sector. The population in this study is manufacturing companies with food and beverage sub-sectors listed on the Indonesia Stock Exchange in 2014-2017. The method of selecting this research sample based on purposive sampling obtained 10 companies during the study period. Testing is done using simple linear regression. The results of the study show that the disclosure of Corporate Social Responsibility (CSR) in the Annual report affects the Abnormal Return. This proves that information about Corporate Social Responsibility (CSR) can be used as a consideration by investors for investment decision making.